(untitled) (Journal of Hama University, 2025)
This researsh aims to comparing Resistance of Teeth Restored by Conventional Fiber Posts and Fiber posts Fabricated by Using the CAD/CAM Technique and their Retention ,the research sample included 32 extracted unidimensional lower first premolars for orthodontic reasons , and the coronal part was cut 2 mm above the cemento-enamel junction. Endodontic treatment was performed. Then the samples were placed within acrylic bases. After that the root canals were prepared to receive the posts. the samples were randomly distributed into 4 groups: Group1: restored with conventional fiber posts Group2 : restored with conventional fiber posts and composite cores buildups and a metal crown Group3 : restored with custom milled fiber posts fabricated by using the CAD/CAM technique Group4 : restored with custom milled fiber posts and cores fabricated by using the CAD/CAM technique and a metal crown All the sample were cemented using self-adhesive resin cement The samples of group 1 and 3 were subjected to pull out forces using the general mechanical testing machine, as a pulling force was applied parallel to the longitudinal axis of the tooth at a speed of 1 mm/min until failure occurred. Statistical tests were carried out using the SPSS (20). The samples of group 2 and 4 were subjected to a compressive load was applied at 90 degree angle at a crosshead speed of 1 mm/min to the long axis of the tooth until fracture occurred. statistical tests were carried out using the SPSS (20).The T student’s test showed that there were statistically significant differences between the mean tensile strengths between the two group 1 and 3 Group1 (106.68 N) Group3 ( 128.15 N) The T student’s test showed that there were statistically significant differences between the mean tensile strengths between the two group 2 and 4 Groub2 (275.24 N) groub 4 (365.51 N) Conclusions Within the limits of this study, the custom milled fiber posts and cores fabricated by CAD/CAM technology showed greater Fracture Resistance and greater retention than the prefabricated fiber posts